2017
DOI: 10.1109/tac.2016.2569432
|View full text |Cite
|
Sign up to set email alerts
|

Contact-Force Control of a Flexible Timoshenko Arm

Abstract: Abstract-This paper discusses a contact-force control problem for a flexible arm. This flexible arm includes a Timoshenko beam, and thus we call it the flexible Timoshenko arm. The aim of the force control is to control the contact force at the contact point. To solve this problem, we propose a simple boundary controller and show the exponential stability of the closed-loop system by the frequency domain method. Finally, we describe simulation results carried out to investigate the validity of the proposed con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 27 publications
0
34
0
Order By: Relevance
“…It will be a more sophisticated and challenging problem to consider the nonlinear coupling of elastic deflection, shear deformation, and angular position in the control. For those cases, the control design is documented in [20,21] to suppress the vibration and rotation of the system. In [20], for the flexible manipulator modeled as the Timoshenko beam, the boundary controllers are designed to eliminate the vibration and rotation of the system under external disturbances.…”
Section: Introductionmentioning
confidence: 99%
“…It will be a more sophisticated and challenging problem to consider the nonlinear coupling of elastic deflection, shear deformation, and angular position in the control. For those cases, the control design is documented in [20,21] to suppress the vibration and rotation of the system. In [20], for the flexible manipulator modeled as the Timoshenko beam, the boundary controllers are designed to eliminate the vibration and rotation of the system under external disturbances.…”
Section: Introductionmentioning
confidence: 99%
“…There have been several relevant studies about the flexible Timoshenko arm based on the hybrid PDE-ODE model (Morgül, 1992;Zhang et al, 1997;Taylor & Yau, 2003;Macchelli & Melchiorri, 2004;Grobbelaar-Van Dalsen, 2010;He, Zhang, & Ge, 2013;Muñoz Rivera, & Ávila, 2015;Endo, Sasaki, & Matsuno, 2017; and references therein). However, many of these studies on hybrid PDE-ODE infinite dimensional settings address only the vibration suppression problem.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the vibration control, the force control, that is the control of the contact force at the contact point where the flexible arm touches an object or the environment, is necessary for realization of more complex tasks (Yoshikawa, 2000;Hokayen & Spong, 2006). Very few studies, Endo, Sasaki, and Matsuno (2017) have investigated the force control problem of the flexible Timoshenko arm. This paper discusses the cooperative control problem of two one-link flexible Timoshenko arms modeled by hybrid PDE-ODE infinite dimensional model.…”
Section: Introductionmentioning
confidence: 99%
“…Endo et al. dedicated to research on the contact‐force control for Timoshenko beam and showed us several difference controllers .…”
Section: Introductionmentioning
confidence: 99%
“…He et al discussed the design of boundary controller for Timoshenko beam and some flexible beams under input and output constraints [22][23][24][25][26]. Endo et al dedicated to research on the contact-force control for Timoshenko beam and showed us several difference controllers [27,28].…”
Section: Introductionmentioning
confidence: 99%